The manager's guide to understanding indemnity clauses - Adoranti, Frank (London : Lessons Professional Pub., 2006)
Understanding Indemnity Clauses explains the differences between fair indemnity clauses and those that are unduly onerous and will give readers an understanding of the nature of indemnities and their potentially devastating effects.
Includes index.
rua 24/12/13
Loans
Keywords: Contracts; Indemnity against liability; Clauses (Law)